2017
DOI: 10.3389/fncel.2017.00148
|View full text |Cite
|
Sign up to set email alerts
|

Reelin Signaling Inactivates Cofilin to Stabilize the Cytoskeleton of Migrating Cortical Neurons

Abstract: Neurons are highly polarized cells. They give rise to several dendrites but only one axon. In addition, many neurons show a preferred orientation. For example, pyramidal neurons of the cerebral cortex extend their apical dendrites toward the cortical surface while their axons run in opposite direction toward the white matter. This characteristic orientation reflects the migratory trajectory of a pyramidal cell during cortical development: the leading process (the future apical dendrite) extends toward the marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 47 publications
0
32
1
Order By: Relevance
“…Rac1 has multiple downstream targets, amongst them it is known to induce the phosphorylation of Cofilin, which promotes actin polymerization (Delorme et al, 2007 ). Furthermore, previous studies have demonstrated that Cofilin is phosphorylated in migrating neurons, downstream to the Reelin pathway, and this activity is important to promote neuronal migration (Chai et al, 2009 ; Frotscher et al, 2017 ). Therefore, E16 brain sections were immunostained with anti-phospho-Cofilin antibodies (Figure 2H ).…”
Section: Resultsmentioning
confidence: 99%
“…Rac1 has multiple downstream targets, amongst them it is known to induce the phosphorylation of Cofilin, which promotes actin polymerization (Delorme et al, 2007 ). Furthermore, previous studies have demonstrated that Cofilin is phosphorylated in migrating neurons, downstream to the Reelin pathway, and this activity is important to promote neuronal migration (Chai et al, 2009 ; Frotscher et al, 2017 ). Therefore, E16 brain sections were immunostained with anti-phospho-Cofilin antibodies (Figure 2H ).…”
Section: Resultsmentioning
confidence: 99%
“…P-LIMK1 inactivates (phosphorylates) Co1lin1, an actin depolymerizing protein of the ADF/Co1lin family. Reelin-mediated inactivation of Co1lin 1 ultimately leads to the stabilization of the actin cytoskeleton and has been implicated in stabilizing LPs of radially migrating cortical neurons as well as in preventing the aberrant tangential migration of neurons of the autonomous nervous system in the spinal cord Maciver and Hussey (2002) , Krüger et al (2010) , Franco et al (2011) , Chai et al (2009) ; Frotscher et al (2017) . To detect a potential misregulation of these downstream events in absence of Reelin signaling, we performed immunoblotting on E14.5 embryonic ventral midbrain tissue for p-LIMK1/LIMK1 and p-Co1lin1/Co1lin1.…”
Section: Resultsmentioning
confidence: 99%
“…In line with these studies, we found that vascular reelin signaling regulates the secretion of Lama-4 by ECs, which in turn has an impact on radial glia attachment to the pial surface and regulates neuronal migration. Although the regulatory mechanisms of Lama-4 deposition are still largely unknown, it has been reported that Lama-4 is accumulated in focal adhesions (60), which might also be influenced by reelin signaling (61).…”
Section: Discussionmentioning
confidence: 99%